Humor in everyday talks: A study of Vietnamese language learner’s communicative competence in intercultural settings - Vũ, Thị Hợi (University of Languages and International Studies, 2017)
Conversational humor in language teaching and learning has risen in prominence since 1990s. Recently, there has been much interest in and debate concerning conversational humor and how it links to participants‟ communicative competence in intercultural situations. However, there has been little empirical study into how humor is used and perceived by its participants, especially when all of them are L2 speakers of English. This research reports on a qualitative study investigating humor used by five L2 speakers of English in their everyday talks. Although the limited number of instances reported means that further research is needed to convincingly make generalizations, it is suggested that humor cannot be perceived as stative and presumptive but as adaptive and emergent resources which are negotiated and context-dependent. Therefore, conversational humor needs to move beyond the traditionally conceived stative and context-independent as innate traits, typical connecting tools to incorporate an awareness of cultural and sociolinguistic differences in using humor and the skills needed to successfully negotiate the meaning of humor in intercultural settings